IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) SEBAGAI PEMBENTUK PENDIDIKAN BERKARAKTER - Febrian, Bella; Paramita, Paramita; Armariena, Dian Nuzulia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— This study aims to describe the similarity of two changes in the structure of short stories of different authors but the content of the story is almost the same. The data source is short story